The relationship between fear and sports injuries among female futsal players - Shimal; Iryna; Magni (VIREF Revista de Educación Física, 2022)
Aims: to identify the relationship between the phenomenon of fear and the occurrence of sports injuries among female futsal players. Method: we applied the survey method with a descriptive approach. The population sample consisted of 82 female players representing seven clubs in the club league in the Kurdistan region-Iraq. The study sample was players n= 48 chosen from four random clubs. It constitutes a 58.5% population time-domain rate for the period from 5/1/2021 to 1/2/2021 for the data collection. The homogeneity component of the sample members was considered, as they are all women aged 19-24 years, had a futsal training history of 3-6 years, and a Body Mass Index from 19-23. Results: researchers recorded that 23 players got injured in 12 marches games, corresponding to 1.9 injuries per game. Moreover, nearly half (48%) of the players experienced injuries during the period, the mean fear score was 5.64 value of computed is 0.98, which is very large and more significant than the tabular (r) value at the degree of freedom 46 and the level of significance 0.05, which is 0.288. There was a correlation between fear and sports injuries among women in the Kurdistan futsal top league. Conclusion: we reached a significant correlation between fear and sports injuries among females in the Kurdistan futsal team. Elite female players are subjected to a significant risk of injury, particularly repeat injuries.